A near-infrared long-afterglow transparent ceramic and a preparation method thereof
Patent Information
- Application Number
- CN202311846485.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-12-28
AI Technical Summary
[0004]在ZnGa2O4长余辉透明陶瓷领域的研究方面,Mevel等人(MEVEL C,CARREAUD J,DELAIZIR G,et al.First ZnGa2O4 transparent ceramics[J].J Eur Ceram Soc,2021,41(9):4934-4941.)采用高能球磨结合放电等离子烧结技术,在未添加烧结助剂的情况下合成了ZnGa2O4:Cr3+长余辉透明陶瓷,经410nm紫光激发后,陶瓷实现了余辉时长超过1.5h、中心波长为694nm的红色长余辉发光;法国波尔多凝聚态材料化学研究所(CHENU S,VERON E,GENEVOIS C,et al.Long-lasting luminescent ZnGa2O4:Cr3+transparent glass-ceramics[J].J Mater Chen,2014,2(46):10002-10010.)采用非晶晶化法制备了ZnGa2O4:Cr3+长余辉透明玻璃陶瓷,陶瓷经410nm紫光激发后获得了时长为60min的红色余辉发光,但以上陶瓷的余辉初始亮度和余辉时长仍不满足应用需求
[0024](1)本发明采用ZnGa2O4为基质,采用离子共掺方法,所制备陶瓷在2000nm处的透过率可达78~83%,余辉时间相比于单掺Cr3+的ZnGa2O4的提升了8~10小时,且余辉发光波段拓宽到了650~800nm。
Smart Images

Figure CN117800605B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of transparent ceramic preparation technology, specifically to a near-infrared long afterglow transparent ceramic and its preparation method. Background Technology
[0002] Near-infrared long-afterglow luminescent materials possess a long luminescence lifetime, and their emission wavelength falls within the near-infrared "optical window." This enables biomedical imaging using these materials to achieve "in-situ excitation-free" imaging, avoiding tissue autofluorescence, background interference, and phototoxicity caused by in-situ excitation, while allowing for deeper tissue penetration. Therefore, the research and development of novel molecular probes based on near-infrared long-afterglow luminescent materials has broad application prospects in biomedical imaging and diagnostic treatment. Among them, the high light transmittance of long-afterglow transparent ceramic materials allows for the effective excitation of all parts, thereby significantly enhancing the ceramic's carrier trapping ability and luminescence uniformity (volume effect).
[0003] Gallate long-afterglow transparent ceramics have become a research hotspot in the field of long-afterglow luminescent materials in recent years. Among them, ZnGa2O4 transparent ceramics are particularly popular due to their stable chemical properties, lack of phase transition at high temperatures, and ease of Zn formation. 2+ and Ga 3+ ZnGa₂O₄ transparent ceramics possess advantages such as the elimination of antisite defects and the ease of achieving near-infrared long afterglow luminescence, making them promising candidates for future development. Currently, ZnGa₂O₄ transparent ceramics are mostly prepared using high-temperature solid-state methods and co-precipitation methods. However, Ga is prone to volatilization under high-temperature vacuum conditions. Although sintering in an oxygen atmosphere can effectively alleviate this problem, issues such as short afterglow time, narrow emission spectrum, and poor optical quality still exist. In recent years, the preparation of transparent ceramics using amorphous crystallization methods has become a new research direction. This process can crystallize the prepared glass to obtain dense transparent ceramics, offering advantages such as low requirements for powder purity, controllable grain size, ease of achieving high optical quality and large-size preparation, and low sintering temperature (usually not exceeding 1100℃), attracting widespread attention.
[0004] In the field of ZnGa2O4 long afterglow transparent ceramics, Mevel et al. (MEVEL C, CARREAUD J, DELAIZIR G, et al. First ZnGa2O4 transparent ceramics[J]. J Eur Ceram Soc, 2021, 41(9):4934-4941.) synthesized ZnGa2O4:Cr using high-energy ball milling combined with spark plasma sintering technology without adding sintering aids. 3+A long-lasting transparent ceramic, after being excited by 410nm violet light, achieved red long-lasting luminescence with an afterglow duration exceeding 1.5 hours and a center wavelength of 694nm; (CHENU S, VERON E, GENEVOIS C, et al. Long-lasting luminescent ZnGa2O4:Cr) 3+ Transparent glass-ceramics[J]. J Mater Chen, 2014, 2(46): 10002-10010.) ZnGa2O4:Cr was prepared by amorphous crystallization method. 3+ Long-afterglow transparent glass-ceramics exhibit a 60-minute red afterglow emission after excitation with 410nm violet light. However, the initial brightness and duration of the afterglow of these ceramics still do not meet application requirements. Therefore, there is an urgent need in this field for a long-afterglow transparent zinc gallate ceramic with high light transmittance and a long afterglow time. Summary of the Invention
[0005] The purpose of this invention is to provide a near-infrared long-afterglow transparent ceramic with good light transmittance and a long afterglow time.
[0006] Another objective of this invention is to provide a method for preparing the above-mentioned near-infrared long-afterglow transparent ceramic, which is easy to operate and can be industrially produced.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] On one hand, the present invention provides a near-infrared long-afterglow transparent ceramic, the general chemical formula of which is:
[0009] (Zn 1-x Eu x (Ga) 1-y Cr y )2O4,
[0010] The range of values for x and y is: 0.03≤x≤0.15, 0.002≤y≤0.02.
[0011] On the other hand, the present invention also provides a method for preparing the above-mentioned near-infrared long afterglow transparent ceramic, which is prepared by an amorphous crystallization method, specifically including the following steps:
[0012] (1) According to the chemical formula (Zn 1-x Eu x (Ga) 1-y Cr yThe stoichiometric ratio of each element in )2O4, 0.03≤x≤0.15, 0.002≤y≤0.02 is used to weigh ZnO, Eu2O3, Ga2O3 and Cr2O3 with a purity greater than 99.99% as raw material powders. The weighed raw material powders, nucleating agent P2O5, network forming body SiO2 and ball milling media are mixed and ball milled in proportion to obtain a mixed slurry.
[0013] (2) Place the mixed slurry obtained in step (1) in a drying oven to dry, and then grind the dried mixed powder thoroughly.
[0014] (3) Pour the powder that has been ground thoroughly in step (2) into an alumina crucible, heat it to melt and anneal it, and then cool it to room temperature in the furnace to obtain a bulk transparent precursor glass;
[0015] (4) The precursor glass obtained in step (3) is further nucleated and crystallized in the furnace to obtain the near-infrared long afterglow transparent ceramic.
[0016] Preferably, in step (1), the amount of nucleating agent added is 0.1 to 1.0 wt.% of the total mass of the raw material powder, and the amount of SiO2 network formed is 0.1 to 1.2 wt.% of the total mass of the raw material powder.
[0017] Preferably, in step (1), the milling medium is anhydrous ethanol, the mass-volume ratio of the amount of milling medium added to the raw material powder is 3g:4-4.5mL, the milling ball is ZrO2 ball, the milling speed is 160-200r / min, and the milling time is 10-18h.
[0018] Preferably, in step (2), the drying time is 10-18h, the drying temperature is 90-120℃, and the grinding time is 0.5-1.5h.
[0019] Preferably, in step (3), the heating and melting process is as follows: at room temperature, the temperature is increased to 950-1100°C at a rate of 5-10°C / min, then increased to 1360-1400°C at a rate of 4-8°C / min, and finally increased to the melting temperature at a rate of 1.5-3°C / min, and held for 6-12 minutes.
[0020] Preferably, in step (3), the annealing temperature is 780-820°C and the time is 5-8 hours.
[0021] Preferably, in step (4), the sintering process for nucleation is as follows: the temperature is increased to 880-920°C at a rate of 5-8°C / min at room temperature, and held for 8-18 hours.
[0022] Preferably, in step (4), the crystallization sintering process is as follows: the temperature is increased to 1100-1150℃ at a rate of 3-5℃ / min at the nucleation temperature, and held for 5-10min.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) This invention uses ZnGa2O4 as the matrix and employs an ion co-doping method. The ceramic prepared by this invention can achieve a transmittance of 78-83% at 2000 nm, and the afterglow time is longer than that of Cr-doped ceramics. 3+ The ZnGa2O4 elongation time was increased by 8–10 hours, and the afterglow emission band was broadened to 650–800 nm.
[0025] (2) The preparation method used in this invention is the amorphous crystallization method, which is easy to prepare ceramics with high light transmittance. All parts of the long afterglow transparent ceramic with high light transmittance can be effectively excited, thereby greatly enhancing the ceramic's ability to capture charge carriers and the uniformity of light emission (volume effect). The transmittance of the ceramic is increased by 18-23%, and the afterglow time of the ceramic is increased by 3-5 hours.
[0026] (3) This invention uses Eu 3+ As a sensitizing ion, it can effectively target Cr. 3+ Energy transfer is carried out, thereby affecting Cr 3+ This transparent ceramic contributes to the afterglow emission of the luminescent center, extending the afterglow time by 4–5 hours. Attached Figure Description
[0027] Figure 1 (Zn) prepared in Example 5 of this invention 0.85 Eu 0.15 (Ga) 0.98 Cr 0.02 Afterglow emission spectrum of 2O4 long-afterglow transparent ceramic.
[0028] Figure 2 (Zn) prepared in Example 5 of this invention 0.85 Eu 0.15 (Ga) 0.98 Cr 0.02 Afterglow decay curve of 2O4 long-afterglow transparent ceramic.
[0029] Figure 3 (Zn) prepared in Example 5 of this invention 0.85 Eu 0.15 (Ga) 0.98 Cr 0.02 Transmittance curve of 2O4 long afterglow transparent ceramic. Detailed Implementation
[0030] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Unless otherwise stated, the raw materials used in the following embodiments are all commercially available products with a purity greater than 99.99%.
[0031] Example 1
[0032] (1) According to the chemical formula (Zn 0.97 Eu 0.03 (Ga) 0.998 Cr 0.002 The raw material powders ZnO, Eu2O3, Ga2O3, and Cr2O3 were weighed in stoichiometric proportions according to their respective elements in 2O4. Using 80 mL of anhydrous ethanol as the ball milling medium, the accurately weighed raw material powders, 0.16 g of nucleating agent P2O5, and 0.06 g of network-forming body SiO2 were placed in a ball mill jar and ball milled at 160 r / min for 12 h to obtain a uniformly mixed slurry. The ball-milled slurry was dried in a 90℃ oven for 18 h, then ground in an agate mortar for 1.5 h, and finally the fully ground powder was poured into an alumina crucible.
[0033] (2) Place the alumina crucible in a muffle furnace and heat it to 950°C at a rate of 5°C / min, then heat it to 1360°C at a rate of 4°C / min, and finally heat it to the melting temperature at a rate of 1.5°C / min and hold it for 6 min.
[0034] (3) Place the alumina crucible in an annealing furnace and anneal at 780°C for 5 hours. After cooling to room temperature in the furnace, a bulk transparent precursor glass is obtained.
[0035] (4) The obtained precursor glass is heated to 880℃ at a rate of 5℃ / min and held for 8h for nucleation, and then heated to 1100℃ at a rate of 3℃ / min and held for 5min for crystallization to obtain the desired ceramic.
[0036] The long-afterglow transparent ceramic prepared in this embodiment has a transmittance of 78% at 2000 nm and an afterglow time of up to 15 hours.
[0037] Example 2
[0038] (1) According to the chemical formula (Zn 0.95 Eu 0.05 (Ga) 0.994 Cr 0.006The raw material powders ZnO, Eu2O3, Ga2O3, and Cr2O3 were weighed in stoichiometric proportions according to their respective elements in 2O4. Using 80 mL of anhydrous ethanol as the ball milling medium, the accurately weighed raw material powders, 0.82 g of nucleating agent P2O5, and 0.36 g of network-forming body SiO2 were placed in a ball mill jar and ball milled at 170 r / min for 13 h to obtain a uniformly mixed slurry. The ball-milled slurry was dried in an oven at 100 °C for 16 h, then ground in an agate mortar for 1.2 h. Finally, the thoroughly ground powder was poured into an alumina crucible.
[0039] (2) Place the alumina crucible in a muffle furnace and heat it to 980°C at a rate of 6°C / min, then heat it to 1370°C at a rate of 5°C / min, and finally heat it to the melting temperature at a rate of 2.0°C / min and hold it for 8 min.
[0040] (3) Place the alumina crucible in an annealing furnace and anneal at 790°C for 6 hours. After cooling to room temperature in the furnace, a bulk transparent precursor glass is obtained.
[0041] (4) The obtained precursor glass is heated to 890℃ at a rate of 6℃ / min and held for 9h for nucleation, and then heated to 1110℃ at a rate of 3.5℃ / min and held for 6min for crystallization to obtain the desired ceramic.
[0042] The long-afterglow transparent ceramic prepared in this embodiment has a transmittance of 79.2% at 2000 nm and an afterglow time of up to 15.8 hours.
[0043] Example 3
[0044] (1) According to the chemical formula (Zn 0.92 Eu 0.08 (Ga) 0.99 Cr 0.01 The raw material powders ZnO, Eu2O3, Ga2O3, and Cr2O3 were weighed in stoichiometric proportions according to the stoichiometric ratio of each element in 2O4. Using 85 mL of anhydrous ethanol as the ball milling medium, the accurately weighed raw material powders, 1.35 g of nucleating agent P2O5, and 0.78 g of network forming body SiO2 were placed in a ball mill jar and ball milled at 180 r / min for 14 h to obtain a uniformly mixed slurry. The ball-milled slurry was dried in an oven at 110 ℃ for 14 h, then ground in an agate mortar for 1 h, and finally the fully ground powder was poured into an alumina crucible.
[0045] (2) Place the alumina crucible in a muffle furnace and heat it to 1000°C at a rate of 7°C / min, then heat it to 1380°C at a rate of 6°C / min, and finally heat it to the melting temperature at a rate of 2.2°C / min and hold it for 10 min.
[0046] (3) Place the alumina crucible in an annealing furnace and anneal at 800°C for 7 hours. After cooling to room temperature in the furnace, a bulk transparent precursor glass is obtained.
[0047] (4) The obtained precursor glass is heated to 900℃ at a rate of 7℃ / min and held for 10h for nucleation, and then heated to 1120℃ at a rate of 4℃ / min and held for 7min for crystallization to obtain the desired ceramic.
[0048] The long-afterglow transparent ceramic prepared in this embodiment has a transmittance of 80.6% at 2000 nm and an afterglow time of up to 16.5 hours.
[0049] Example 4
[0050] (1) According to the chemical formula (Zn 0.9 Eu 0.1 (Ga) 0.985 Cr 0.015 The raw material powders ZnO, Eu2O3, Ga2O3, and Cr2O3 were weighed in stoichiometric proportions according to their respective elements in 2O4. Using 90 mL of anhydrous ethanol as the ball milling medium, the accurately weighed raw material powders, 1.56 g of nucleating agent P2O5, and 0.86 g of network-forming SiO2 were placed in a ball mill jar and ball milled at 190 r / min for 15 h to obtain a uniformly mixed slurry. The ball-milled slurry was dried in an oven at 115 °C for 12 h, then ground in an agate mortar for 0.8 h. Finally, the fully ground powder was poured into an alumina crucible.
[0051] (2) Place the alumina crucible in a muffle furnace and heat it to 1050°C at a rate of 8°C / min, then heat it to 1390°C at a rate of 7°C / min, and finally heat it to the melting temperature at a rate of 2.6°C / min and hold it for 11 min.
[0052] (3) Place the alumina crucible in an annealing furnace and anneal at 810°C for 7.5 hours. After cooling to room temperature in the furnace, a bulk transparent precursor glass is obtained.
[0053] (4) The obtained precursor glass is heated to 910℃ at a rate of 7.5℃ / min and held for 14h for nucleation, and then heated to 1135℃ at a rate of 4.5℃ / min and held for 8min for crystallization to obtain the desired ceramic.
[0054] The long-afterglow transparent ceramic prepared in this embodiment has a transmittance of 81.7% at 2000 nm and an afterglow time of up to 16.5 hours.
[0055] Example 5
[0056] (1) According to the chemical formula (Zn 0.85 Eu0.15 (Ga) 0.98 Cr 0.02 The raw material powders ZnO, Eu2O3, Ga2O3, and Cr2O3 were weighed in stoichiometric proportions according to their respective elements in 2O4. Using 90 mL of anhydrous ethanol as the ball milling medium, the accurately weighed raw material powders, 1.63 g of nucleating agent P2O5, and 0.95 g of network-forming body SiO2 were placed in a ball mill jar and ball milled at 200 r / min for 18 h to obtain a uniformly mixed slurry. The ball-milled slurry was dried in an oven at 120 ℃ for 10 h, then ground in an agate mortar for 0.5 h, and finally the fully ground powder was poured into an alumina crucible.
[0057] (2) Place the alumina crucible in a muffle furnace and heat it to 1100°C at a rate of 10°C / min, then heat it to 1400°C at a rate of 8°C / min, and finally heat it to the melting temperature at a rate of 3°C / min and hold it for 12 min.
[0058] (3) Place the alumina crucible in an annealing furnace and anneal at 820°C for 8 hours. After cooling to room temperature with the furnace, a bulk transparent precursor glass is obtained.
[0059] (4) The obtained precursor glass is heated to 920℃ at a rate of 8℃ / min and held for 18h for nucleation, and then heated to 1150℃ at a rate of 5℃ / min and held for 10min for crystallization to obtain the desired ceramic.
[0060] Figure 1 (Zn) prepared for this embodiment 0.85 Eu 0.15 (Ga) 0.98 Cr 0.02 The emission spectrum of 2O4 long-afterglow transparent ceramics shows strong luminescence in the range of 650–800 nm.
[0061] Figure 2 To measure the prepared (Zn) using an afterglow meter 0.85 Eu 0.15 (Ga) 0.98 Cr 0.02 The afterglow decay curve of 2O4 long-afterglow transparent ceramic shows that the afterglow time can reach 18 hours after the excitation of the irradiation source (UV 254nm) is stopped.
[0062] Figure 3 (Zn) prepared for this embodiment 0.85 Eu 0.15 (Ga) 0.98 Cr 0.02 The transmittance curve of 2O4 long afterglow transparent ceramic shows that the transmittance at 2000 nm is 83%.
[0063] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the scope of the technology disclosed in the present invention, and within the spirit and principles of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A near-infrared long-afterglow transparent ceramic, characterized in that, The general chemical formula of this ceramic is: (Zn 1-x I x (Ga 1-y Cr y )2O4, in x and y The value range is: 0.03≤ x ≤0.15, 0.002≤ y ≤0.
02.
2. A method for preparing the near-infrared long-afterglow transparent ceramic according to claim 1, characterized in that, The amorphous crystallization method is used for preparation, specifically including the following steps: (1) According to the chemical formula (Zn 1-x Eu x (Ga) 1-y Cr y )2O4, 0.03≤ x ≤0.15, 0.002≤ y The stoichiometric ratio of each element in ≤0.02 is used to weigh ZnO, Eu2O3, Ga2O3 and Cr2O3 with a purity greater than 99.99% as raw material powders. The weighed raw material powders, nucleating agent P2O5, network forming body SiO2 and ball milling media are mixed and ball milled in proportion to obtain a mixed slurry. (2) Place the mixed slurry obtained in step (1) in a drying oven to dry, and then grind the dried mixed powder thoroughly; (3) Pour the powder that has been ground thoroughly in step (2) into an alumina crucible, heat to melt, anneal, and cool to room temperature in the furnace to obtain a bulk transparent precursor glass; (4) The bulk transparent precursor glass obtained in step (3) is further nucleated and crystallized in the furnace to obtain the near-infrared long afterglow transparent ceramic.
3. The method for preparing a near-infrared long-afterglow transparent ceramic according to claim 2, characterized in that, In step (1), the amount of nucleating agent added is 0.1 to 1.0 wt.% of the total mass of the raw material powder, and the amount of SiO2 network formed is 0.1 to 1.2 wt.% of the total mass of the raw material powder.
4. The method for preparing a near-infrared long-afterglow transparent ceramic according to claim 2, characterized in that, In step (1), the milling medium is anhydrous ethanol, the mass-volume ratio of the milling medium to the raw material powder is 3g:4-4.5mL, the milling ball is ZrO2 ball, the milling speed is 160-200r / min, and the milling time is 10-18h.
5. The method for preparing a near-infrared long-afterglow transparent ceramic according to claim 2, characterized in that, In step (2), the drying time is 10-18h, the drying temperature is 90-120℃, and the grinding time is 0.5-1.5h.
6. The method for preparing a near-infrared long-afterglow transparent ceramic according to claim 2, characterized in that, In step (3), the heating and melting process is as follows: at room temperature, the temperature is increased to 950-1100℃ at a rate of 5-10℃ / min, then increased to 1360-1400℃ at a rate of 4-8℃ / min, and finally increased to the melting temperature at a rate of 1.5-3℃ / min, and held for 6-12 minutes.
7. The method for preparing a near-infrared long-afterglow transparent ceramic according to claim 2, characterized in that, In step (3), the annealing temperature is 780-820℃ and the time is 5-8h.
8. The method for preparing a near-infrared long-afterglow transparent ceramic according to claim 2, characterized in that, In step (4), the sintering process for nucleation is as follows: the temperature is increased to 880-920℃ at a rate of 5-8℃ / min at room temperature, and held for 8-18 hours.
9. The method for preparing a near-infrared long-afterglow transparent ceramic according to claim 2, characterized in that, In step (4), the crystallization sintering process is as follows: the temperature is increased to 1100-1150℃ at a rate of 3-5℃ / min at the nucleation temperature, and held for 5-10min.
Citation Information
Patent Citations
Method for preparing magnesium aluminate spinel transparent ceramic through amorphous crystallization
CN114988863A
Preparation method of spinel type zinc gallate long-afterglow luminescent transparent ceramic
CN115304366A